Comparing and contrasting White and African American participants' lived experiences in drug court. Issue 2 (2nd April 2016) - Gallagher, John R.; Nordberg, Anne
ABSTRACT: Drug courts are designed to offer treatment in lieu of incarceration for nonviolent offenders who have substance use disorders. Recent evidence has suggested the African American participants are less likely to graduate drug court than their White counterparts. This qualitative study interviewed 38 participants from a midwestern drug court to compare and contrast Whites' ( n = 22) and African Americans' ( n = 16) lived experiences in the program in order to learn about the factors that may contribute to racial disparities in outcomes. Findings suggest that both White and African American participants felt that the drug court team was supportive and compassionate and wanted them to succeed in the program. White participants found managing the demands of drug court with other obligations they had to be a noticeable challenge, and they also reported continued alcohol use in the program even though the program required total abstinence. African Americans were most critical of the quality of substance abuse treatment they received and felt that they were forced to accept culturally incompetent labels. Findings have implications for drug court practice and future research.